(untitled) (Management Dynamics, 2024)
Food insecurity is becoming an alarming global challenge. It is more severe in the Global South. This study aimed to examine the food insecurity in local communities in the Dolpa district of Karnali province, a remote region in northwestern Nepal. The study used a convergent parallel mixed research design to explain food insecurities and community resources to mitigate them in Thulo Bheri and Tripurasundari municipalities in Dolpa. A survey was conducted among 388 households between September and November 2024. A structured questionnaire on food security measurement frameworks was used to evaluate household experiences of food insecurity. Six key informant interviews supplemented the survey results. The study found that factors such as remoteness, ruggedness, inaccessibility, and low crop variety determine the state of food security in the isolated municipalities of the Himalayan region. These factors also determine local food production, consumption, and nutritional intake. Therefore, due to an uncertain state of local food availability, food insecurity remains high in the study area, especially in the Thulo Bheri municipality, with only 46.13% of households sustaining for 7-9 months annually for sufficient food. Despite these situations, food resilience is achieved by local households through the long-standing economic opportunities and resources within communities. Community resources include earnings from herbs, food aid, and barter systems among households during shortages and high-demand times of the year. The study concludes that strengthening long-standing local options and targeted food supply systems can form food resilience in the region.